Lokalna sieć pomocy i wsparcia dla nieletnich matek na przykładzie społeczności miasta Boppard w Niemczech = A local support and assistance network for adolescent mothers in the community of Boppard, Germany - Magda, Ernest; Treml, Johanna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This article delineates the institutional support framework for adolescent pregnant women and those who have given birth and are part of the local community of the town of Boppard, Germany. Through in-depth interviews with young mothers, the study outlines the diverse challenges these women face in their difficult life situations.
Keywords: pomoc; wsparcie; nieletnie matki; assistance; support; adolescent mothers